Development of Dry Walnut Shell Edible Film Plasticized with Glycerol and/or Sorbitol and Incorporated with Aloe Vera Gel and Lemon Essential Oil - Girgin, Berika; Tugrul, Nurcan (BUDAPEST UNIV TECHNOLOGY ECONOMICS, 2023)
Edible packaging films produced from biomaterials are environmentally friendly, promising alternatives against synthetic plastics films. The aim of this study was to produce a low-cost edible film from waste dry walnut shell by casting method. Effects of the plasticizer type and concentration, lemon essential oil (LEO) and aloe vera gel (AVG) addition on edible films properties were investigated. Produced edible films characterization analysis were realized by Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR). Moisture content, water vapor transmission rate (WVTR), water solubility, swelling index, thicknesses and color parameters of the produced edible films were investigated. Moisture content of the films was decreased between 23.3-50.6% after LEO and AVG addition, except the moisture content of the film plasticized with 20% sorbitol was increased by 518%. WVTR of the films were increased between 8.7-72.3% after LEO and AVG addition due to the hydrophobic character of LEO. Glycerol plasticized edible films water solubility were decreased between 27.3-75.9%, sorbitol plasticized edible films water solubility were increased between 237.5-100.8% with LEO and AVG incorporation. The swelling index of C1 was reduced by 51.5%, C2 was reduced by 62.4%, C4 was reduced by 36.1%. The swelling index of the C3 was increased by 10.5%, C5 was increased by 21.5%. LEO and AVG addition increased to the film thickness maximum 79.2%. Total color changes (Delta E) of glycerol plasticized films were higher than sorbitol plasticized film. The edible film produced can be used in food packaging due to the appropriate physical and barrier properties.
Keywords: dry walnut shell; lemon essential oil; aloe vera gel; glycerol; sorbitol; STRUCTURAL-CHARACTERIZATION; ANTIMICROBIAL PROPERTIES; MECHANICAL-PROPERTIES; COMPOSITE FILMS; COATINGS; ADSORPTION; POWDER; Engineering